1999
DOI: 10.1007/s003450050159
|View full text |Cite
|
Sign up to set email alerts
|

The development of bacterial biofilms on indwelling urethral catheters

Abstract: The biofilm mode of growth has been implicated in the majority of human bacterial infections. In the urinary tract, notable biofilm-associated infections include prostatitis, chronic cystitis, struvite urolithiasis, and catheter-associated infections. Biofilms protect the causative organisms from host defences and antimicrobial therapy. Biofilm formation has traditionally been considered to result from adhesion and capsule formation by adherent microorganisms. Recent work has shown that a large number of genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
129
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(133 citation statements)
references
References 45 publications
2
129
0
2
Order By: Relevance
“…Most complications with a LTC are encrustation-related catheter blockage, and 50% of catheter users are troubled with this problem [2,[6][7][8]. All available types of indwelling catheters are susceptible to encrustation [9], in addition to catheterassociated infections and urosepsis [10]. Data from the BioMed Catheter Clinic has introduced the idea of managing such patients with blocked or/and encrusted catheters in a dedicated clinic, equipped with facilities such as flexible cystoscope, enabling patients to be treated in an environment that meets their needs and potentially reduces the risk of catheter problems at a later date and more complex bladder stone removal [4].…”
Section: Discussionmentioning
confidence: 99%
“…Most complications with a LTC are encrustation-related catheter blockage, and 50% of catheter users are troubled with this problem [2,[6][7][8]. All available types of indwelling catheters are susceptible to encrustation [9], in addition to catheterassociated infections and urosepsis [10]. Data from the BioMed Catheter Clinic has introduced the idea of managing such patients with blocked or/and encrusted catheters in a dedicated clinic, equipped with facilities such as flexible cystoscope, enabling patients to be treated in an environment that meets their needs and potentially reduces the risk of catheter problems at a later date and more complex bladder stone removal [4].…”
Section: Discussionmentioning
confidence: 99%
“…Enteroinvasive and enteropathogenic isolates, on the other hand, express little or no curli at either temperature (4). Recently it has been realized that the majority of human bacterial infections are biofilm related (6,24). Anderson et al (1) reported that E. coli formed the intracellular biofilmlike pods in urinary tract infections of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Crystal formation occurs due to the urease-catalysed hydrolysis of urea into ammonia, leading to an increase in the local pH and the precipitation of calcium, magnesium and phosphate ions (Morris et al, 1999). The pathogenesis of P. mirabilis UTIs is not at present understood fully.…”
Section: Introductionmentioning
confidence: 99%